Pengaruh Pupuk Organik pada Pengolahan Lahan di Desa Dahana - Iren Forjun Telaumbanua; Priska Rahmat Yanti Zega; Manyupril Lukevin Fatlow Zai; Faristina Laia; Natalia Kristiani Lase (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
The use of organic fertilizers in agriculture in Dahana Village has significant potential in improving soil fertility and crop productivity. Organic fertilizers, which are derived from natural materials such as agricultural waste and animal manure, serve to improve soil structure, increase water retention capacity, and provide nutrients needed by plants. This study explored different methods of applying organic fertilizers and their impact on plant growth and the quality of agricultural produce. Results show that organic fertilizer not only improves vegetative growth but also yield quality, making it an essential component in sustainable agricultural practices. Thus, this study emphasizes the importance of integrating the use of organic fertilizers in land management strategies to achieve optimal and sustainable agricultural yields in Dahana Village.